2011
DOI: 10.1007/s10336-011-0796-9
|View full text |Cite
|
Sign up to set email alerts
|

Is the transition from biparental to male-only care in a monogamous seabird related to changes in body mass and stress level?

Abstract: In a number of species with biparental care, the parents of one sex desert the mate and brood before the chick is independent. The reasons for this desertion are poorly understood. In the study reported here we investigated whether sex-specific changes in body mass corrected for size (in short body mass) and the stress-related heterophil to lymphocyte ratio (H:L) during the late incubation and chick-rearing period are related to female brood desertion in a small Arctic seabird, the Little Auk (Alle alle). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 49 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…Chicks reach their peak body mass (120-124 g, max 150 g) at the age of 19-24 days, and fledge weighing 110-114 g on average (Stempniewicz 1980(Stempniewicz , 2001. Body mass recession preceding fledging may be associated with a reduction in feeding frequency (females cessate feeding before fledging, probably due to a sex-specific role in parental care during and after fledging and/or an ancestral pattern of parental care; Wojczulanis-Jakubas et al 2011), tissue maturation and/or might be an essential prerequisite for efficient flight (Ricklefts 1968;Gaston 1985;Taylor and Konarzewski 1989;Stempniewicz 1980Stempniewicz , 2001. The fledging age of chicks varies among individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Chicks reach their peak body mass (120-124 g, max 150 g) at the age of 19-24 days, and fledge weighing 110-114 g on average (Stempniewicz 1980(Stempniewicz , 2001. Body mass recession preceding fledging may be associated with a reduction in feeding frequency (females cessate feeding before fledging, probably due to a sex-specific role in parental care during and after fledging and/or an ancestral pattern of parental care; Wojczulanis-Jakubas et al 2011), tissue maturation and/or might be an essential prerequisite for efficient flight (Ricklefts 1968;Gaston 1985;Taylor and Konarzewski 1989;Stempniewicz 1980Stempniewicz , 2001. The fledging age of chicks varies among individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of sex differences in BKC, SMI and blood parameters (H/L ratio, numbers of heterophils, lymphocytes and all leucocytes per 10 000 RBC) throughout the breeding season deny the hypothesis that little auk females desert the brood earlier than the male because of body reserve depletion. Previous studies on temporal variation of body condition variables also do not support this hypothesis (Jakubas et al , Wojczulanis‐Jakubas and Jakubas , Wojczulanis‐Jakubas et al , ).…”
Section: Discussionmentioning
confidence: 83%
“…and ), reflecting carry‐over effects from previous phases of breeding (egg incubation, chick brooding and feeding). Previous studies have also reported lower SMI in adult little auks during chick rearing compared to earlier phases of the breeding cycle (Taylor , Wojczulanis‐Jakubas et al , but see Wojczulanis‐Jakubas et al ). Mass loss during breeding, also observed in other alcids [e.g.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations